About the Possibilities of Registration of Drug Influence by Means of Radiocardiographic Function Analysis - Lösel, E.; Kleine, N.; Hoffmann, G. (Nuklearmedizin - NuclearMedicine, 1981)
Changes in cardiac dynamics were analyzed by means of radiocardiographic function analysis under an infusion of epinephrine using the method of RAB. Typical changes in heart rate, stroke volume and blood pressure were observed after the application of epinephrine. Compared to examinations under physical exercise in case of healthy control subjects there was no typical decrease of enddiastolic volume dependent on the heart rate. Ejection time and ejection velocity were placed within the variation compared to values of a control group under physical exercise but there was a steeper increase of the curve under the effect of epinephrine. Under the influence of SolcoserylR no significant change could be observed in this series of tests compared to the basic values. The effect of epinephrine was changed by SolcoserylR in the way of an essentially smaller rise in heart rate and of a definite prolongation in diastolic time. A change in ejection time under the influence of epinephrine after the application of SolcoserylR could not be found. This allows the conclusion, that under the influence of SolcoserylR and after the administration of epinephrine better conditions for the metabolic restitution of heart muscle are given and consequently a direct effect of SolcoserylR on the heart muscle can be assumed.